2010
DOI: 10.1249/mss.0b013e3181bf94d6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Delivery Mode on the Urinary Excretion of Nandrolone Metabolites

Abstract: Peak 19-NA concentrations were higher, and occurred later, when the 19-norandrostenedione was added to a solid supplement. This may be due to a slower rate of absorption and/or a reduced diuresis, resulting in a longer period for the metabolites to accumulate in the urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…If a protein powder contained 90 ng/g of a steroid such as nandrolone or one of its precursors, this would appear as a negative test if the limit of detection is set at 100 ng/g. However, a 25 g portion of this product would deliver a dose of 2.3 μg of the steroid and there is a good chance that this might result in a positive test for nandrolone if a sample was collected within a few hours of ingestion of the supplement (Watson et al, 2009(Watson et al, , 2010. Even when a product batch is tested prior to release for sale, there may still be a risk, albeit a very low risk.…”
Section: Quality Assurance Programsmentioning
confidence: 99%
“…If a protein powder contained 90 ng/g of a steroid such as nandrolone or one of its precursors, this would appear as a negative test if the limit of detection is set at 100 ng/g. However, a 25 g portion of this product would deliver a dose of 2.3 μg of the steroid and there is a good chance that this might result in a positive test for nandrolone if a sample was collected within a few hours of ingestion of the supplement (Watson et al, 2009(Watson et al, , 2010. Even when a product batch is tested prior to release for sale, there may still be a risk, albeit a very low risk.…”
Section: Quality Assurance Programsmentioning
confidence: 99%
“…Creatine has also been reported to have antioxidant properties, but these are relatively minor, and creatine supplementation, at least in a rat swimming model, does not reduce markers of oxidative stress, inflammation, and muscle damage . This picture seems to suggest that a number of agents with antioxidant or anti-inflammatory properties may have some effects on free radical-mediated responses, but whether this is beneficial or harmful is not known (Peternelj & Coombes, 2011;Urso & Sawka, 2013). Potentially harmful effects include a blunting of training responses and an attenuation of radical-mediated physiological processes.…”
Section: Promoting Recovery Between Training Sessionsmentioning
confidence: 99%
“…Recent reports have also indicated that the presence of even extremely small amounts of some agents will result in a positive test. Analysis of urinary responses to the ingestion of small amounts of a nandrolone precursor (19-norandrostenedione; Watson et al, 2009Watson et al, , 2010 has revealed a high risk of a positive test: Ingestion of a 1.0 µg dose of 19-norandrostenedione in 500 ml of water produced no values that were above the current World Anti-Doping Agency threshold for a positive doping test (2 ng/mL), but five subjects (of 20) tested positive when 2.5 µg was ingested, and 15 subjects had urinary 19-norandrostenedione concentrations exceeding the threshold when 5.0 µg of the steroid was ingested. These are extremely low levels of contamination.…”
Section: Potential Harmful Effects Of Supplement Usementioning
confidence: 99%
“…The potential for consumption of contaminated dietary supplements by an athlete, which could result in a failed drug test, is now well established 1–6. A number of studies of the prevalence of contaminated supplements have been published, suggesting that between 3 and 25% of supplements can contain low quantities of steroids or stimulants that are not specified on the label 1, 7–8, 12.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies of the prevalence of contaminated supplements have been published, suggesting that between 3 and 25% of supplements can contain low quantities of steroids or stimulants that are not specified on the label 1, 7–8, 12. The relevance of this contamination to a drug‐tested athlete is clear with several studies confirming the potential for ingestion of contaminated supplements to result in a positive doping test 1–3, 5–6. In a recent administration study in which male and female subjects ingested just 5 g of a creatine supplement that had been deliberately ‘contaminated’ with 2.5 µg of a nandrolone precursor (19‐norandrostenedione), analysis of urine samples revealed that 25% of the subjects would have failed a drug test for nandrolone under World Anti‐Doping Agency (WADA) rules 13.…”
Section: Introductionmentioning
confidence: 99%